A nonlinear synthetic unit hydrograph method that accounts for channel network type - Czyzyk, Kelsey A., author; Niemann, Jeffrey D., advisor; Gironás, Jorge, committee member; Ronayne, Michael J., committee member (Colorado State University. Libraries, 2018)
Stormflow hydrographs are commonly estimated using synthetic unit hydrograph (UH) methods, particularly for ungauged basins. Current synthetic UHs either consider very limited aspects of basin geometry or require explicit representation of the basin flow paths. None explicitly considers the channel network type (i.e., dendritic, parallel, pinnate, rectangular, and trellis). The goal of this study is to develop and test a nonlinear synthetic UH that explicitly accounts for the network type. The synthetic UH is developed using kinematic wave travel time expressions for hillslope and channel points in the basin. The effects of the network structure are then isolated into two random variables whose distributions are estimated based on the network type. The proposed method is applied to ten basins from each classification and compared to other related methods. The results suggest that considering network type improves the estimated UHs with the largest improvements seen for dendritic, parallel, and pinnate networks.
Keywords: kinematic wave; spatially distributed; unit hydrograph; network classification; drainage network; travel time